Peripheral Arterial Disease and Spinal Cord Injury: A Retrospective Nationwide Cohort Study. Issue 41 (October 2015) - Su, Ta-Wei; Chou, Tzu-Yi; Jou, Herng-Jeng; Yang, Pei-Yu; Lin, Cheng-Li; Sung, Fung-Chang; Hsu, Chung-Y.; Kao, Chia-Hung
Abstract : Abstract: The aim of this study was to elucidate the relationship between spinal cord injury (SCI) and the risk of peripheral arterial disease (PAD) in a cohort study with a large representative sample. The National Health Insurance Database was used to select patients who were diagnosed from 2000 to 2010. Patients with a history of PAD were excluded. The SCI group comprised 42, 673 patients diagnosed with SCI, and we enrolled 170, 389 matched controls (non-SCI group). We used a Cox proportional hazards regression model to analyze the adjusted risk of PAD between the case and control patients. Patients with SCI exhibited a significantly higher risk (hazard ratio [HR] = 1.37; 95% confidence interval [CI] = 1.22–1.53) of PAD than patients without SCI. Patients with diabetes were at the highest risk of developing PAD (adjusted HR = 3.11, 95% CI = 2.80–3.44). Among patients without comorbidity, SCI patients exhibited a significantly higher risk of PAD than non-SCI patients. Furthermore, lumbar, sacral, or coccygeal spine, and multiple spine SCI were significantly associated with an increased risk of PAD (HR = 1.56, 95% CI = 1.33–1.84, HR = 2.11, 95% CI = 1.59–2.79, respectively). SCI is associated with an increased risk of PAD. Future studies should focus on modifying risk factors to reduce PAD risk among patients with SCI.